Chemotherapy for patients with advanced lung cancer with interstitial lung disease: a prospective observational study. (June 2022) - Koda, Keigo; Enomoto, Yasunori; Aoshima, Yoichiro; Amano, Yusuke; Kato, Shinpei; Hasegawa, Hirotsugu; Matsui, Takashi; Yokomura, Koshi; Mochizuki, Eisuke; Matsuura, Shun; Koshimizu, Naoki; Morita, Meiko; et al.
Introduction: Although recent advances in chemotherapy for lung cancer are remarkable, most clinical trials have excluded patients with interstitial lung disease (ILD) due to the concern of developing acute exacerbation (AE) of ILD. Hence, accumulating original evidence of cancer treatment for this population is important. Methods: Between 2016 and 2020, a prospective observational study was conducted across 11 Japanese hospitals. Patients with chemotherapy- naïve, inoperable, advanced lung cancer with ILD were included. The primary outcome was the frequency of AE-ILD after registration; the secondary outcomes were the risk factor of AE-ILD and the efficacy of chemotherapy. Results: Among 124 patients enrolled, 109 patients who received chemotherapy were analyzed. The median age was 72 years, and the majority showed usual interstitial pneumonia (UIP)/probable UIP pattern upon chest computed tomography. The median percent-predicted forced vital capacity (%FVC) was 81% (interquartile range: 66–95%). After registration, 23 patients (21.1%; 95% confidence interval [CI]: 14.4–29.7%) developed AE-ILD. The logistic analysis revealed that lower %FVC slightly but significantly increased the risk of AE-ILD (odds ratio per 10% decrease: 1.27; 95% CI: > 1.00–1.62). Overall response rates/median overall survival times in non-small-cell lung cancer and small-cell lung cancer for the first-line chemotherapy were 41% (95% CI: 31–53)/8.9 months (95% CI: 7.6–11.8) and 91% (95% CI: 76–98)/12.2 months (95% CI: 9.2–14.5), respectively. Conclusion: AE-ILD during chemotherapy is a frequent complication among patients with lung cancer with ILD, particularly those with lower %FVC. Conversely, even in this population, passable treatment response can be expected.